Isometric mid-thigh pull force-time characteristics: A good indicator of running performance - Lum, D.; Chua, K.; Aziz, A. R. (Journal of Trainology, 2020)
Objectives: The relationship between force-time characteristics obtained from isometric mid-thigh pull (IMTP) and endurance running performance has not been studied. The purpose of this study was to investigate the relationships between force-time characteristics obtained from IMTP with indicators of endurance running performance. Design and Methods: Participants attended a familiarisation session to be familiarised with all testing protocols. Subsequently, they completed the IMTP and a 2.4-km run time trial (2.4-kmTT) on the first testing session. Post 48-72 h of the first session, they then performed a running economy (RE) test at 12km.h-1 and graded exercise test on the second testing session. Results: Significant inverse correlations between all IMTP measures and 2.4kmTT was observed (r=-0.53 to -0.78, p<0.01). Similarly, all IMTP measures were significantly correlated to maximal aerobic speed (r=0.38 to 0.66, p<0.05) except Force at 150 ms. There were significant correlations between IMTP peak force, net peak force and rate of force development (0-150 ms) with lower limb stiffness (r=0.41 to 0.49, p<0.05). Force at 100 ms and all rate of force development measures were significantly correlated to RE (r=-0.44 to -0.68, p<0.05). Conclusion: Findings showed that measures obtained from IMTP are good indicators of endurance running performance and can provide insights into the force generating capability required by endurance runners. In addition, the significant correla-tions between strength measures and running performance suggest that muscular strength may be an important determinant of running performance.